Biogenic amines and other polar compounds in long aged oxidized Vernaccia di Oristano white wines. (September 2018) - Tuberoso, Carlo Ignazio Giovanni; Serreli, Gabriele; Montoro, Paola; D'Urso, Gilda; Congiu, Francesca; Kowalczyk, Adam
Abstract: Oxidized white wines are produced by techniques that provide a barrel ageing which can range from a few years to some decades. This step, characterized by the metabolic activity of peculiar strains of Saccharomyces cerevisiae yeast, can affect the chemical composition of these wines and the production of unwanted substances such as biogenic amines. In this study, Vernaccia di Oristano wines from different vintages have been analysed for the first time regarding the content of biogenic amines and amino acids (by HPLC-FLD), and polar compounds (by HPLC-DAD and LC-MS). Furthermore, colour and technological parameters (contents of alcohol, reducing sugars, total and volatile acidities, pH and organic acids) of the wines were also evaluated. Older samples showed dark shades, which may have derived from polyphenols' oxidation while ageing. Some typical ageing products, such as 5-(hydroxymethyl)furfural and hydroxycinnamic acid derivatives were found in larger quantities in these samples, as well as the purinic compound xanthine, which was also detected in relevant concentrations. Additionally, as expected, the average of the main biogenic amines quantified in Vernaccia di Oristano was higher compared to non-oxidized white wines, especially in the older samples. Thus, though this content does not exceed values which spoil the quality of the wine, the monitoring of the winemaking conditions is suggested, to further limit the presence of these undesirable compounds. Graphical abstract: Unlabelled Image Highlights: Sherry-like wine Vernaccia di Oristano had relative high amount of biogenic amines. HPLC-FLD analysis revealed putrescine as the main biogenic amine. Untargeted LC-ESI-FT (Orbitrap) MS analysis was undertaken on the samples. HPLC-DAD analysis showed a good content in gallic acid and hydroxycinnamic acids.